Hubungan Cyberbullying Dengan Kesehatan Mental Remaja Di Smk Muhammadiyah 1 Patuk Gunungkidul Yogyakarta Tahun 2025 - Jamroni; Luthfiah Al-Zalmasry; Anis Khotimah; Pramukti Dian S (STIKes Ibnu Sina Ajibarang, 2025)
The advancement of information technology and social media has significantly influenced adolescents, bringing both benefits and challenges. One of the negative impacts is cyberbullying, a form of digital harassment that may harm mental health, leading to stress, anxiety, and depression. This study aims to examine the prevalence of cyberbullying and its relationship with adolescents’ mental health at SMK Muhammadiyah 1 Patuk Gunungkidul, Yogyakarta. Using a quantitative cross-sectional design, the study involved 50 twelfth-grade students selected through total sampling. Data were collected using validated and reliable questionnaires. Results showed that 72% of respondents experienced high levels of cyberbullying, while 28% reported lower levels. Mental health among respondents was generally moderate to low, reflecting the adverse effects of cyberbullying on psychological well-being. The findings indicate that higher exposure to cyberbullying increases the vulnerability of adolescents to mental health problems. Preventive measures such as digital literacy, parental and school support, and counseling services are essential to mitigate its impact.